Prostatic adenocarcinoma with mandibular metastasis - Kritika Saxena (Wolters Kluwer Medknow Publications, 2019)
Metastatic lesions of primary tumors comprise almost 1% of different types of oral cancers. These lesions can affect either bones or soft tissues in the maxillofacial region. Whenever the maxillofacial area is affected, the most common location is in the molar region of the mandible. A 70-year-old male patient, presented with swelling in the jaw region, of acute onset. Clinical, radiological, and histological examinations were carried out. Finally, it was diagnosed to be a metastatic lesion in the jaw, with the primary lesion being in the prostate gland. The clinical presentation of mandibular metastasis follows a pattern characterized by irradiated dental pain in the third molar region. Differential diagnosis and treatment of these patients can be extremely difficult because there are several pathologic conditions with similar symptoms.